Effects of Autologous Microfragmented Adipose Tissue on Healing of Tibial Plateau Levelling Osteotomies in Dogs: A Prospective Clinical Trial - Luca Pennasilico; Caterina Di Bella; Sara Sassaroli; Alberto Salvaggio; Francesco Roggiolani; Angela Palumbo Piccionello (Animals, 2023)
The aim of this study was to evaluate the effects of autologous microfragmented adipose tissue (MFAT) applied after mechanical fragmentation and assess these effects radiographically in bone healing in dogs subjected to tibial plateau levelling osteotomy (TPLO). Twenty dogs with unilateral cranial cruciate ligament disease were enrolled and randomly assigned to the treatment group (MFAT) or the control group (NT). The MFAT group underwent TPLO and autologous MFAT intra-articular administration, while the NT group underwent TPLO alone. Adipose tissue was collected from the thigh region, and MFAT was obtained by mechanical fragmentation at the end of the surgery. The patients were subjected to X-ray examination preoperatively, immediately postoperatively (T0), and at 4 (T1) and 8 (T2) weeks postoperatively. Two radiographic scores that had previously been described for the evaluation of bone healing after TPLO were used. A 12-point scoring system (from 0 = no healing to 12 = complete remodelling) was used at T0, T1, and T2, while a 5-point scoring system (from 0 = no healing to 4 = 76–100% of healing) was used at T1 and T2. The median healing scores were significantly higher at T1 and T2 for the MFAT group compared with the NT group for the 12-point (p < 0.05) and 5-point (p < 0.05) scoring systems. The intra-articular injection of autologous microfragmented adipose tissue can accelerate bone healing after TPLO without complications.